Outbreak of pseudotuberculosis in commercial guinea fowls (Numida meleagris) - Luca Bano; Angela Guolo; Marta Vascellari; Monia Cocchi; Fabrizio Agnoletti; Ilenia Drigo; Michela Bonci (Italian Journal of Animal Science, 2010)
The present paper reports an outbreak of pseudotuberculosis in guinea fowls reared for meat production. The clinical and pathological features as well as the results of the laboratory investigations are described. To the knowledge of the authors this is the first reported case of Yersinia pseudotuberculosis infection in guinea-fowls.